TOWARDS URBAN TRANSFORMATION FOR SUSTAINIBILITY OF IBU KOTA NUSANTARA - Wibisono, Rizky Bangun; Mawardi, Rafi Aufa (Jurnal Politik Pemerintahan Dharma Praja, 2023)
This research delves comprehensively into the development prospects of Ibu Kota Nusantara (IKN) within the context of the visionary Green Forest City and the inclusive City for All concept. Employing qualitative research methods and a literature review approach, the study draws from a diverse array of scholarly sources, including academic journals, articles, news reports, and more. The findings underscore the imperative need for cross-sectoral synergy, involving government bodies, private enterprises, and civil society organizations, to realize the vision of inclusivity in IKN's development. The future trajectory of IKN necessitates the implementation of systemic mechanisms for achieving inclusive cities. These mechanisms include augmenting political participation among minority groups, ensuring universal access to egalitarian public services, extending legal protection and social services to all, including minority groups and individuals with disabilities, and establishing inclusive healthcare and educational facilities. Successful execution of these dimensions holds the potential to transform IKN into an inclusive city, offering a sense of safety and comfort for its entire population. In conclusion, this research underscores the significance of holistic collaboration and systemic approaches in building inclusive urban environments. It illuminates the path towards realizing the Green Forest City's vision and the City for All concept within the context of IKN, with implications extending to the broader realm of urban development.